Pemilihan Penerima Beasiswa Menggunakan Metode Profile Matching - Agus Junaidi; Fany Visella (Paradigma, 2017)
To help in establishing the determination of students eligible scholarship then needed an analysis relating to anyone students who receive scholarships.One method for analysis of this decision is to use a matching profile. This method was chosen because it can help as a decision supporting the granting of scholarships to students who deserve it. This method also provides information in the form of data which students qualify for scholarships so that motivates their efforts in making the learning process in schools. Research done by the academic aspect of assessment on criteria, aspects of personality, and economic aspects of the family which include the average income a month, dependent parents, and vehicles. After this method is then determined aspects will find the difference (gap) between the profile with the State data from the students and further specified percentage of both aspects and elements together and then do a rank process will determine the optimal alternative, i.e. students who deserve a scholarship. Using profile matching then the process of determining which students will get scholarship can be done quickly and accurately.